Anticancer effect of Copper Activated Plasma Water on MCF7 Breast Cancer Cells - Umaru, Isaac John; Kingsly, Iseko Iyoko; Ogochukwu, Edom Favour; Akafa, Tensaba Andes; Malantso, Jackson Soyinka; Habibu, Bilyaminu; Umaru, Kerenhappuch Isaac (African Journal of Clinical Medicine and Pharmacy Research, 2025)
Broad biological activities of “plasma-activated water” (PAW) have drawn great attentions recently. Treatment of water using gas discharge plasma led to acidic solutions with excellent and broad antibacterial activity. Because PAW caused severe membrane damages in bacteria and diffused freely in extracellular matrix, PAW also demonstrated good anti-biofilm activity. However, further studies revealed that trace amounts of metal ions (mainly copper) in PAW brought by plasma treatment played key roles in bacteria inactivation. The contribution of metal ions to the antibacterial activity varied among PAWs from different working gases. However, solution acidification caused by reactive species in plasma was essential. The experimental results demonstrated that potential artifacts in reported biological activities of PAWs should be considered. Therefore, Copper has important redox activity and can participate in various biochemical reactions by accepting and donating electrons. As a trace element, thus, Anticancer effect of Copper Activated Plasma Water on MCF7 Breast Cancer Cells. Materials and method, used are a non-thermal micro-hollow cathode discharge (MHCD) was used to generate plasma-activated waters (CU-PAWs), The MCF-7 human breast adenocarcinoma cell line (IBRC C10082), and 3-(4,5 dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) was acquired. Cell Viability Measurements; After 48 h of incubation 0.5 mg/ml MTT (20 μl) was added to the control and experimental cells and the cells were incubated for 3 h in a CO2 incubator at 37 °C, Measurement of Reactive Oxygen Species (ROS) and Flow Cytometry was conducted. Results: The 3- and 4-min CU-PAW reduced MCF-7 cells viability to approximately 62% and 56% of control (p< 0.01), respectively. However, in the cases of 1- and 2-min CU-PAW cell proliferation did not diminish significantly as compared with the control group (p> 0.05). This observation is consistent with earlier studies, which illustrated that plasma irradiation reduced cell viability in a time-dependent manner. Thus, in this research, DOX (0.45 µM) combined with 3- or 4-min CU-PAW killed MCF-7 cell efficiently (44% and 39% cell viability, respectively; p< 0.01) than DOX (54% cell viability) or 3- or 4-min CU-PAW alone (63% and 56% cell viability, respectively). These was in line with a that PAW plus cisplatin at low doses reduced viability of human endometrial carcinoma more effectively than cisplatin or PAW alone. Conclusion: Although further investigations are crucial, CU-PAW combined with DOX could be a promising cancer treatment strategy, contributing to a more positive therapeutic agent.